Experimental investigation of bacterial concrete using Portland slag cement - Dharmabiksham, B.; Murali, K. (AIP conference proceedings, 2023)
Weathering, flaws, ground subsidence, seismic disturbances, and human effort are all examples of frequent strategies used to produce cracks and fractures in concrete structures, hence shortening the service life of the structures. The use of microorganisms to biomineralize calcium carbonate is a novel strategy for healing or remediating deteriorated or damaged structures. A novel strategy to micro naturally propelled calcium carbonate precipitation is described in this research (MICCP). Using this approach, you may increase the compressive strength and stiffness of your concrete mix. The calcite layer enhances the permeability of the specimen, hence enhancing its resistance to soluble, sulphate, and thaw damage, among other things. On the subject of bacteria, the present research investigates the impacts of Pseudomonas aeruginosa on the properties of Portland slag cement concrete. A series of tests are carried out to identify the properties of Standard Concrete and the characteristics of concrete containing microscopic organisms at a concentration of 109 cells/ml and then to compare the two. The attributes of bacterial concrete are established by calculating the value of water intake, the tensile stress, and the compressive strength of the concrete, and then comparing and managing the concrete properties. According to the results of the experiments, microbes have a substantial impact on the compressive strength of concrete when compared to Standard Concrete at a certain confluence of bacteria in this study. The impact of microorganisms on the tensile strength of concrete is quite obvious. At 28 days, 56 days, and 91 days, the compressive strength of bacterial concrete is greater than 35.55 percent, 26.33 percent, and 19.94 percent, respectively. Furthermore, as compared to control concrete, the tensile stress of bacterial concrete at 28, 56, and 91 days is greater than 32.97 percent, 37.93 percent, and 21.52 percent, respectively, at each of the three time points. At 28, 56,and 91 days, the flexural strengths of bacterial concrete were more than 10.72 percent, 13.11 percent, and 12.53 percent, respectively. After 28 days, 56 days, and 91 days, the water absorption of bacterial concrete was found to be 20.95 percent, 25.97 percent, and 12.56 percent lower than that of control concrete, respectively. When compared to control concrete, bacterial concrete demonstrated a significant increase in compressive strength and tensile stress during the duration of the experiment.